The role of immunosuppression in long-term graft hepatitis and fibrosis after paediatric liver transplant – comparison of two treatment protocols - Haller, Wolfram; Hodson, James; Brown, Rachel; Lloyd, Carla; Hubscher, Stefan; McKiernan, Patrick; Kelly, Deirdre (Frontiers in Transplantation, 2023)
Background&Aims: We have previously demonstrated high rates of chronic allograft hepatitis and fibrosis in liver transplant patients on long-term cyclosporine monotherapy. We subsequently changed practice to add low-dose prednisolone to maintenance treatment with tacrolimus post-transplant. The aim of the study was to assess the impact of the immunosuppression change on graft histopathology. Methods: Patients treated in this era (Tac+Pred, 2000-2009, N=128) were compared to a historical cohort, who had been maintained on a steroid-free, cyclosporine-based regime (CSA-Only, 1985-1996, N=129). Protocol liver biopsies and laboratory tests were performed five- and ten-years post-transplant in both groups. Results: Compared to CSA-Only, the Tac+Pred cohort had significantly lower rates of chronic hepatitis (CH) at five (20% vs. 44%, p<0.001) and ten (15% vs. 67%, p<0.001) years post-transplant, with similar trends observed in inflammation and fibrosis at five years. The Tac+Pred cohort had significantly lower hepatic transaminases and IgG levels and was less likely to be autoantibody positive at both time points. However, the degree of graft fibrosis at ten years did not differ significantly between eras (p=0.356). Conclusion: Increased immunosuppression effectively reduced chronic allograft hepatitis and fibrosis at 5 years, suggesting it is an immunologically driven variant of rejection. However, there was no significant reduction in the degree of fibrosis at ten years, indicating a multifactorial origin for long term graft fibrosis.